Highly efficient processable molybdenum trioxide as a hole blocking interlayer for super-yellow organic light emitting diode - Talik N.A.; Woon K.L.; Yap B.K.; Wong W.S.; Whitcher T.J.; Chanlek N.; Nakajima H.; Saisopa T.; Songsiriritthigul P. (Institute of Physics Publishing, 2023)
Aluminum compounds; Electron affinity; Fluorine compounds; Lithium Fluoride; Luminance; Nanobelts; Organic light emitting diodes (OLED); Sodium hydroxide; Transition metal oxides; Transition metals; Ultraviolet photoelectron spectroscopy; Efficiency enhancement; Energetic barriers; Hole blocking layers; Luminance efficiency; Molybdenum trioxide; Optimal thickness; Poly(p-phenylenevinylene); Solution-processed; Molybdenum oxide